Network virtualization in cloud IaaS (IEEE, 2015)
In this tutorial, we are going to dive deeper into Cloud Networking, in particular just as we have studied compute virtualization, and storage virtualization, we are going to study network virtualization, which is perhaps the most interesting and the most recent development of the three. We will look at Network protocols and components and how they relate to the internal operating systems in the cloud. We will study examples of network services in IaaS systems of AWS and OpenStack. Finally we will cover the topic of load balancing, which is a special networking feature that is extremely useful in cloud computing